Determinants of financial instrument disclosure patterns of Australian listed resource firms pre- and post-IFRS adoption - Taylor, Grantley J. (Curtin University, 2008)
This thesis investigates the pattern of Financial Instrument Disclosures (FIDs) within the annual reports of Australian listed extractive resource companies (mining and petroleum) over a four year longitudinal period encompassing the 2003 to 2006 financial years. This is an important period to investigate FID patterns as it encompasses those years leading up to and immediately following formal adoption of the Australian equivalents to the International Financial Reporting Standards (IFRS).Using an index (FIDI) comprising 120 items of financial instrument information to measure the extent of FIDs, there is a statistically significant increase in disclosures over the four year period with the greatest percentage increase occurring on transition to IFRS. Under IFRS, direct comparability with firms internationally can be made. Although the financial instrument disclosure requirements are the same pre- and post- IFRS adoption, the introduction of a new form of regulation makes a difference to managements’ financial reporting disclosure incentives. Total financial instrument disclosures, as measured by FIDI, increased from 34% in Yr 1 (year ending 31 December 2002 or year ending 30 June 2003) to 52% in Yr 4 (year ending 31 December 2005 or 30 June 2006), the latter representing the first full year annual reporting period under IFRS. Similar trends are observed for mandatory financial instrument disclosures (comprising 57 items) and discretionary financial instrument disclosures (comprising 63 items).The results of the main model regression analysis demonstrate that the independent variables of corporate governance, capital management, overseas listing and income tax characteristics of firms are factors which are variably significantly associated with FID patterns for panel data. Statistically significant associations are achieved for pooled regression results. Control variables comprising firm size, leverage, top 20 shareholder concentration, sub-industry and return on assets are statistically significant predictor variables of financial instrument disclosures. In contrast, overseas stock exchange listing of firms and additional income tax characteristics that are related to financial reporting transparency are found to be significantly negatively associated with FID patterns.Discrete items that comprise FIDI are individually statistically significantly associated with the independent and control variables. Similarly, discrete items that comprise the independent variable scores are individually statistically significant predictor variables of financial instrument disclosures. This thesis contributes to an understanding of the extent, trends and rationale behind resource firms’ financial instrument disclosure practices in Australia. Further, this thesis examines the association of financial instrument disclosures with corporate governance, capital management, overseas listing and income tax characteristics of firms leading up to and immediately following IFRS adoption in Australia.